Fast and simple fabrication of SiO2/poly(vinylidene fluoride) coated cotton fabrics with asymmetric wettability via a facile spray-coating route. Issue 6 (March 2019) - Yu, Rongrong; Tian, Mingwei; Qu, Lijun; Zhu, Shifeng; Ran, Jianhua; Liu, Ruichao
Cotton fabrics with hydrophilic-to-hydrophobic asymmetric surfaces are attractive as potential utilizable structures for functional garments. The spray-coating route could be deemed as a fast and simple way to achieve asymmetric surfaces. In this paper, SiO2 nanoparticles with size ∼ 205 nm were synthesized via the modified sol-gel method, and then modified with poly(vinylidene fluoride) (PVDF) to form a hydrophobic surface. The SiO2 nanoparticles modified with PVDF were uniformly deposited on the outer surface of cotton fabric aided with the robust air flow force from the sprayer. The morphology and chemical structures were characterized by scanning electron microscopy, mapping, atomic force microscopy, X-ray photoelectron spectroscopy and Fourier-transform infrared spectroscopy. The results indicated that SiO2 nanoparticles were evenly deposited on the surface of cotton fibers and stable interfacial interaction occurred between SiO2 and PVDF molecular chains. The existence of SiO2 could increase the roughness of the fabric surface, which could enhance the water-repellent property of the coated fabrics. Furthermore, the water-repellent property and thermal insulation properties were evaluated via the water contact angle and thermal conductivity tests, respectively, and the results showed that 20 wt.% SiO2 /PVDF fabric achieved a desirable level of contact angle, 136.6°, which was the largest water contact angle among all the samples, and the lowest thermal conductivity of 0.033 W/mK, resulting from the existence of SiO2 nanoparticles. Such a fast and simple spray-coating strategy could be widely introduced into asymmetric fabric modification, and such asymmetric fabrics with reasonable water-repellent and thermal insulating outer surfaces could act as candidates in the field of functional garments.